Associated factors of prolonged hospital stay among adult dengue fever patients in Hospital Raja Perempuan Zainab II - Nawi, Mohd Shamril Mohd (2017)
Background: Dengue fever is regarded as one of the most common vector-borne related diseases in Malaysia. In Kelantan, most of dengue cases is reported from Kota Bharu district. Although dengue research is done extensively in Malaysia, very few studies done to determine the prevalence of prolonged hospital stay and its associated factors. Objective: The objectives of this study were to determine the prevalence of prolonged hospital stay among adult dengue patients in Hospital Raja Perempuan Zainab II in 2015-2016 and its associated factors. Methodology: This was a cross sectional study involving 302 adult patients who were admitted in 2015-2016 for dengue fever in Hospital Raja Perempuan Zainab II, Kota Bharu, Kelantan. Data was collected in January 2017. The research tool that was used for data collection was a designed proforma. Data were analysed using SPSS version 23.0. Multiple logistic regression analysis was performed to determine the associated factors for prolonged hospital stay. Results: The mean (SD) age of adult dengue patient in this study was 33.46 (8.32) years old. Out of 302 patients, 29.1% of them have prolonged hospital stay. The mean length for hospital stay is 64.47 ± 31.26 hours. . The study also noted that factors associated with longer hospital stay among dengue patient werelethargy/restlessness, severe plasma leakage/ dengue shock syndrome and severe organ involvement. Conclusion: Prevalence for prolonged hospital stay among adult dengue patient is high. Patients with lethargy/restlessness, severe plasma leakage/dengue shock syndrome and severe organ involvement should be given more importance in term of management to avoid longer hospital stay among dengue fever patient.